Pengaruh Produk, Harga, Lokasi dan Promosi Terhadap Keputusan Pembelian Donat Pada J.CO Donuts & Coffee Jember - Damayanti, Dian Risky; Kurniawati, Dewi (Politeknik Negeri Jember, 2023)
The increasingly competitive business competition with many similar products released by competitors is the background for research. J.CO Donuts & Coffee Jember is a company that launched donuts as a product it offers and has many competitors. The aim of this research was to test and analyze the influence of product, price, location and promotion on donut purchasing decisions at J.CO Donuts & Coffee Jember. A sample of 50 respondents was taken from the consumer population who purchased donuts directly. The analytical tool used in this research is multiple linear regression analysis with the help of SPSS 23.00 for Windows. The conclusion from the results of this research is that product, price, location and promotion variables simultaneously have a significant influence on the decision to purchase donuts at J.CO Donuts & Coffee Jember. Partially, the results of this research concluded that the product, price and promotion variables partially had no significant effect on purchasing decisions, while location partially had a significant effect on purchasing decisions. Based on the analysis, location is the variable that has a dominant influence on the decision to purchase donut products at J.CO Donuts & Coffee Jember.